Determinants of Household Cooking Energy Choice: Are Such Choices Influenced by Health Outcomes? - Oyedele, Ovikuomagbe (International Journal of Energy Economics and Policy, 2023)
Several factors determine a woman’s choice of cooking fuel type for her household. Since there are health effects to such decisions, it is consequential that households would take into consideration their health outcome experiences when making such choices. This study examined the determinants of household’s cooking energy choice. It examined whether such choices are influenced by health outcomes. A multinomial logit model was estimated, controlling for possible heterogeneity. Higher levels of household wealth index and education promote cleaner energy use such as electricity and gas rather than firewood, charcoal and other solid fuels in both urban and rural locations. Increasing household size reduced the likelihood of household’s use of electricity and gas rather than firewood, charcoal and other solid fuels. Richer households were generally more likely to use than poorer households. This was irrespective of whether they had zero child death or at least one child death experience. Thus, policy effort towards achieving energy transition and environmental quality should improve household wealth and women education.